Improving the EMI-based damage detection in composites by calibration of AD5933 chip. (February 2021) - Wandowski, T.; Malinowski, P.H.; Ostachowicz, W.M.
Highlights: The need for AD5933 chip calibration. A simple mid-point frequency calibration of AD5933 obtaining correct EMI results. Detection of delamination with different sizes under various temperatures achieved. Cheap and simple solution equivalent to costly and professional impedance analyser. Abstract: In this paper results of calibration of Analog Devices AD5933 chip for damage detection problems based on electromechanical impedance (EMI) are presented. A simple calibration method using mid-frequency point and resistor with known resistance was utilised. Authors investigated the influence of calibration process on the measurement results and its agreement with professional measurement equipment. Results obtained from AD5933 were compared with results obtained by professional impedance analyser HIOKI IM3570. Moreover, the influence of lack and wrong calibration of the AD5933 chip is presented. Calibration was validated for the case of damage detection in the carbon fibre reinforced polymer CFRP panel with delamination. Damage indices in the form of RMSD and CCD were utilised. Influence of changing temperature was also included and compensated. Good agreement of results from AD5933 and HIOKI IM3570 was achieved in the case of EMI spectra as well as calculated damage indices. The EMI spectra of magnitude of impedance, phase angle, resistance, conductance, reactance and susceptance were investigated. The obtained results pave the way for effective employment of the AD5933 chip for damage assessment in composite structures.